Digital Literacy: Text Credibility on Critical Reading Material - Leliana, Ayunita; Harti, Laily Maulida Septiana; Zuhri, Fauris; Kusumaningtyas, Dwi Cahyani Sri (JET ADI BUANA, 2021)
With the onset of the digital era, the classroom's teaching and learning process has also shifted. The use of technology makes it easy for lecturers and students to access various information and references on the internet. However, not all of the information and concerns come from reliable and credible sources, so it is necessary to select and sort out the references used. This research's background determines students' ability to find and utilize and evaluate the credibility of information to be used in their writing. Although most students can use digital technology in their daily lives, they have difficulty determining whether the articles or texts from the internet come from credible sources or just subjective opinions that are not strong enough to be used as references in the 2018 class. Students' skills have an impact on the search for reference sources when they write scientific papers. The preliminary observations on students of 2018 and 2019 have shown that some students stated that they were very familiar with information technology and accessed the internet skillfully. Some had difficulty finding the required references. The output of this research is a guide for checking the credibility of references and articles published in journals so that the public can refine the findings of this study by providing contributive input. If the results are positive, it means that they can be applied to other courses in other classes as well.